2019
DOI: 10.1080/2162402x.2019.1625687
|View full text |Cite
|
Sign up to set email alerts
|

Intratumorally delivered formulation, INT230-6, containing potent anticancer agents induces protective T cell immunity and memory

Abstract: The benefits of anti-cancer agents extend beyond direct tumor killing. One aspect of cell death is the potential to release antigens that initiate adaptive immune responses. Here, a diffusion enhanced formulation, INT230-6, containing potent anti-cancer cytotoxic agents, was administered intratumorally into large (approx. 300mm 3) subcutaneous murine Colon26 tumors. Treatment resulted in regression from baseline in 100% of the tumors and complete response in up to 90%. CD8 + or CD8 + /CD4 + T cell double-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
6
2
Order By: Relevance
“…This is consistent with the hypothesis that INT230-6 enhances immune cell infiltration, possibly due to the higher number of epitopes available in the tumor, as a consequence of the localized cell death (necrosis) consistently observed. Enhanced immune cells infiltration was also observed in our recently published article [ 33 ], where CD8+ cells were observed in the tumor at different time points after treatment. INT230-6 IT and the capability of these cells in specifically killing Colon-26 cells was demonstrated in vitro.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with the hypothesis that INT230-6 enhances immune cell infiltration, possibly due to the higher number of epitopes available in the tumor, as a consequence of the localized cell death (necrosis) consistently observed. Enhanced immune cells infiltration was also observed in our recently published article [ 33 ], where CD8+ cells were observed in the tumor at different time points after treatment. INT230-6 IT and the capability of these cells in specifically killing Colon-26 cells was demonstrated in vitro.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, the involvement of the immune cells after treatment is also supported by the inability of tumors to grow in animals having had a complete response upon re-challenge. More in depth immune infiltrating immune cell analysis on INT230-6 is reported (see Bloom [ 33 ])…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, higher-grade lesions and metastatic sites could potentially be treated by intratumoral injection. We have shown that direct intratumoral injection of PAM could inhibit the growth of MDA-MB-231 xenografts [64], and image-guided intratumoral injection has become an accepted delivery route for immunotherapies in melanoma and other tumor types [65,66]. This includes anti-PD1 antibody (pembrolizumab ) delivered via the DfuseRx platform [67] or EBC-46 (tigilanol tiglate) [68].…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that accumulation of tumor specific lipids in the tumor microenvironment can affect the expression of CD1d on both tumor cells and DCs, thereby suppressing their immunogenicity and facilitating eventual immune evasion. Immunogenic cell death as a result of intratumoral treatment of tumors with anti-cancer agents can lead to release of tumor-specific antigens, which then can activate T-cell mediated immunity and confer long term immunologic memory against tumor (94). The use of EPA/DHA alone or in combination with various chemotherapeutic agents has shown anti-tumor effects, mostly via apoptosis (92).…”
Section: Effects Of Altered Lipids On Nkt Cell Functionsmentioning
confidence: 99%